Measles Vaccine Coverage and Disease Outbreaks: A Systematic Review of the Early Impact of COVID-19 in Low and Lower-Middle Income Countries - Packham, Alice; Taylor, Alice E.; Karangwa, Marie-Paule; Sherry, Emma; Muvunyi, Claude; Green, Christopher A. (International Journal of Public Health, 2024)
Objectives: We aimed to evaluate changes to measles-containing vaccine (MCV) provision and subsequent measles disease cases in low- and lower-middle income countries (LICs, LMICs) in relation to the COVID-19 pandemic. Methods: A systematic search was conducted of MEDLINE, OVID EMBASE and PubMed records. Primary quantitative and qualitative research studies published from January 2020 were included if they reported on COVID-19 impact on MCV provision and/or measles outbreak rates within LICs and LMICs. Results: 45 studies were included. The change in MCV1 vaccination coverage in national and international regions ranged -13% to +44.4% from pre-COVID time periods. In local regions, the median MCV1 and overall EPI rate changed by –23.3% and -28.5% respectively. Median MCV2 rate was disproportionally impacted in local areas during COVID-interruption time-periods (-48.2%) with ongoing disruption in early-recovery time-periods (-17.7%). 8.9% of studies reported on vaccination status of confirmed measles cases; from these, 71-91% had received no MCV dose. Conclusion: MCV vaccination coverage experienced ongoing disruption during the recovery periods after initial COVID-19 disruption. Vaccination in local area datasets notably experienced longer-term disruption compared to nationally reported figures.